Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/foods12040891
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hermetic Storage of Wet Maize and Its Effect on Quality

Abstract: Maize is a major crop grown in many regions of the world for human consumption, starch production, and animal feed. After harvest, maize is dried to avoid spoilage caused by fungal growth. However, in the humid tropics, drying maize harvested during the rainy season poses challenges. In such instances, temporary storing maize under hermetic conditions may preserve grain quality while waiting for conditions suitable for drying. Wet maize at the moisture contents (m.c.) of 18, 21, and 24% was stored for up to 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Previous research has documented no changes in the m.c. of grain stored in hermetic bags after several weeks [ 20 , 30 ]. The change in m.c.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has documented no changes in the m.c. of grain stored in hermetic bags after several weeks [ 20 , 30 ]. The change in m.c.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that, during hermetic storage, the germination decreases more rapidly as the m.c. increases [ 21 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations